DEVELOPMENT OF TECHNOLOGY FOR ANODE BALL PRODUCTION - G. V. Kozhevnikova (Литьë и металлургия)
Technology of copper anode balls manufacturing by means of cross-wedge rolling method is developed. The technology satisfies the requirements towards anode balls’ crystalline structure, form and geometrical dimensions accuracy.